2008
DOI: 10.1177/1362168807084494
|View full text |Cite
|
Sign up to set email alerts
|

The effect of processing instruction and dictogloss tasks on acquisition of the English passive voice

Abstract: input-based focus on form technique, to dictogloss tasks, an output-oriented focus-on-form type of instruction to assess their effects in helping beginning-EFL (English as a Foreign Language) learners acquire the simple English passive voice. Two intact classes of Grade 7 beginning EFL learners (n ϭ 110) in China were randomly assigned to each type of instruction: Group A (n ϭ 55) to processing instruction (PI), and Group B (n ϭ 55) to dictogloss tasks (DG). A pretest and posttest (immediate and delayed) desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 20 publications
7
78
3
Order By: Relevance
“…Ever since VanPatten and Cadierno (1993) published their original study, a large body of research has mushroomed comparing PI to different kinds of PBI such as traditional instruction (TI; e.g., VanPatten & Cadierno, 1993), meaning-based output instruction (MOI; e.g., Farley, 2001), meaning-based drills instruction (MDI; e.g., Keating & Farley, 2008), communicative output (CO; e.g., Toth, 2006) and dictogloss tasks (DG; e.g., Qin, 2008;VanPatten, Inclezan, Salazar, & Farley, 2009). For instance, VanPatten and Cadierno's study (1993) investigated possible differences in the effectiveness of PI and TI on the acquisition of direct object pronouns in Spanish.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever since VanPatten and Cadierno (1993) published their original study, a large body of research has mushroomed comparing PI to different kinds of PBI such as traditional instruction (TI; e.g., VanPatten & Cadierno, 1993), meaning-based output instruction (MOI; e.g., Farley, 2001), meaning-based drills instruction (MDI; e.g., Keating & Farley, 2008), communicative output (CO; e.g., Toth, 2006) and dictogloss tasks (DG; e.g., Qin, 2008;VanPatten, Inclezan, Salazar, & Farley, 2009). For instance, VanPatten and Cadierno's study (1993) investigated possible differences in the effectiveness of PI and TI on the acquisition of direct object pronouns in Spanish.…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…In addition, some studies found that PI and PBI students performed equally well on the acquisition of the Spanish subjunctive (Collentine, 1998;Farley, 2004b) and English passive voice (Qin, 2008). Attributing the equal performance of the groups to the nature of the structure, these studies argued that it was the efficacy of PBI, not the ineffectiveness of PI, that enabled PBI learners to receive more "incidental input" (Farley, 2004b, p. 168) and thus to be "more PI-like than intended" (Farley, 2004b, p.167).…”
Section: Processing Instruction and Production-based Instructionmentioning
confidence: 99%
“…Recent research on focus-on-form has sought ways to draw learners' attention to linguistic forms without isolating these forms from their meaningful context; dictogloss tasks have sometimes been used in these investigations (e.g., Kowal & Swain, 1997;Qin, 2008). As one of the leading researchers in the use of tasks in a focus-on-form context, Swain (1998) argues that while engaged in a dictogloss task, L2 learners' attention could be drawn to target forms during LREs while the primary focus is meaning.…”
Section: Dictogloss Tasks and Opinion-gap Tasksmentioning
confidence: 99%
“…Therefore, DG has the potential to integrate communicative notions with the traditional concerns of grammar instruction (Al-Sibai, 2008;Pica, 1997), to work as a form-focused technique (Jacobs & Small, 2003;Shak, 2006) in which students aim not to reproduce the text word-for-word but rather to best approximate its meaning and style and to allow for the so-called 'meta-talk' or 'language related episodes', occasions in which students discuss or question their language use as they engage in a reconstruction task in L2 (Qin, 2008;Rashtchi & Khosroabadi, 2009).…”
Section: Analysis and Correctionmentioning
confidence: 99%
“…A good body of local and international research exists on the effect of dictogloss on language learning (e.g., Abbasian & Mohammadi, 2013;Han, 2011;Nabei, 1996;Khoii & Pourhassan, 2015;Kooshafar et al, 2012;Prince, 2013;Purwaningsih & Kurniasih, 2014;Qin, 2008;Uludag & Vanpatten, 2012). However, to the best of these researchers' knowledge, other than a lone study by them (Bataineh & Bani Younis, 2016), none exists on the effect of DG-based training on teacher writing instruction and student written performance.…”
Section: Significance Of the Studymentioning
confidence: 99%